REVITALISASI GIZI ANAK ANTI STUNTING MELALUI DIVERSIFIKASI SUSU SEGAR - Prodyanatasari, Arshy; Purnadianti, Mely; Jayanti, Krisnita Dwi (Universitas Islam Malang, 2024)
Poor nutrition can cause stunting in children, where children grow short. Blimbing Village is one of the villages in Mojo District, Kediri Regency that raises dairy cows, but the cow's milk products have not been processed optimally. Based on the above, an effort is made to make nutritional value products made from fresh milk and can increase the selling value of dairy products. This PkM activity was carried out through five stages, namely giving pretest, education, demonstration, product tester, and post-test. Education was given about the benefits, processing, and storage of fresh milk and a demonstration of making Silky Strawberry Milk. At the end of the PkM activity, the Silky Strawberry Milk product that had been made was distributed to the participants. Silky Strawberry Milk can be an alternative dessert to meet children's nutritional needs and prevent stunting and become an alternative business to improve the economy of the community and village MSMEs. This PkM activity can increase the knowledge of participants, this is known from the increase in the average post-test score obtained, which is 94.22. Nutrasetics product innovations that utilise natural resources based on local wisdom need to be improved. This is done as an effort to manage, empower, and increase the economic value of these natural resources. In addition, nutrasetika innovation products can fulfil the fulfilment of nutrition and nutrition of children during growth, thus minimising the occurrence of stunting.